Antecedents of philanthropic attitude and its impact on prosocial behavior during the Syrian conflict - Aldairany, Shaza (2021)
Individual philanthropy is a precious resource in any society. The significance of philanthropy greatly increases during periods of conflicts when institutions collapse and societal needs multiply. However, the current knowledge of the phenomenon has been overlooked, while the philanthropic theory itself continues to develop. To date, most literature has focused primarily on international volunteers, paid professional work and western elite philanthropists rather than local volunteers, although they play important roles during conflict. The Syrian conflict offers research opportunities on philanthropy and prosocial behaviour. This is because the situation in Syria quickly shifted from a state with limited philanthropy to an encouraging and impressive one. The purpose of this thesis is to examine the antecedents of philanthropic attitude and prosocial behavior during the Syrian conflict of both residents of the country and its diaspora. The thesis also aims to explore the lived experience of individual Syrians. In doing so, it provides a solid foundation for understanding individual philanthropy during periods of conflict based on indigenous views. Using a concurrent mixed-methods approach, the thesis developed a conceptual framework and investigated the experience from local points of view. Theory of planned behavior and identification model are the underpinning theories in this study. The sample of population included five hundred respondents and 20 interviews. In line with the thesis's triangulation design, findings from both methods were used to strengthen the validity of the results. The quantitative findings suggested that attitude shapes prosocial behavior in the Syrian conflict. Philanthropic attitude and prosocial behaviour are result from the interactions of some personal values, subjective norms, and the degree of trust in society. Unexpectedly, religiosity has no clear effect on Syrians philantrophic attitude and prosocial behavior. Findings from the qualitative study suggested prosocial behaviour mechanisms during the conflict corresponded to the current literature in terms of the forms of prosocial behavior and motivations of philanthropy. However, the locals expressed fear and guilt have a great impact on their philanthropic action. The thesis makes original contributions to knowledge, researchers, and communities. It extends the theory of planned behaviour and provides a conceptual framework based on attitude. In addition, it empirically draws a roadmap of Syrian philanthropy and its mechanisms. The thesis provides implications that improves the local capabilities by changing their mindset towards individual philanthropy in conflict locations